Negative Poisson's ratio in non‐porous smooth curve sheet. Issue 5 (5th January 2017) - Tan, Huifeng; Yu, Lin; Zhou, Zhengong
Abstract : The microstructure of the manmade auxetic materials always involve inherited porosity and sharp corners, where the stress concentration occurred. We have proposed a novel kind of non‐porous smooth curve sheet which exhibits a negative Poisson's ratio and has a low stress concentration factor. The auxetic response was validated by good qualitative and quantitative agreements between the tensile experiments and numerical analysis of array model. Using the experimentally validated finite element model, the parametric study on the evolution of the macroscopic Poisson's ratio, the stress concentration factor on the geometry parameters and the parental material properties were investigated. This one phase auxetic smooth curve sheet, which is simple to manufacture and assemble into 3D structures, may be used in a variety of industrial applications.